The Effectiveness of Online Learning Through Undiksha E-Learning During the Covid-19 Pandemic in the Physical Education Study Program - Satyawan, I Made; Wahjoedi, Wahjoedi; Swadesi, I Ketut Iwan (Journal of Education Technology, 2021)
The effectiveness of Undiksha e-learning as one of the official learning media for the Undiksha Physical and Health Study Program has not been measured scientifically. This study aims to describe the effectiveness of online learning using Undiksha E-Learning in the Physical Education and Health Study program during the COVID-19 pandemic. This research is descriptive quantitative research with a survey design. The sample of this study was all students of the Physical Education Study Program, amounting to 120 people. The data collection instrument uses a questionnaire packaged into google forms. Data analysis used descriptive statistics. The results showed that online learning using Undiksha's E-Learning during the covid-19 pandemic in the Physical Education and Health Study program was quite effective. This is revealed from online learning using Undiksha E-Learning, the concentration of students in paying attention to the explanations of the lecturers is 96%, the level of student understanding of learning materials is 88%, student motivation in participating in online learning using Undiksha E-Learning is 77%, and on student learning outcomes classified as 88%. The results of the study show that online learning using Undiksha's E-Learning during the covid-19 pandemic in the Physical Education and Health Study program is quite effective. The results of this study have implications for the sustainability of the use of Undiksha e-learning as a learning platform used by Undiksha lecturers and students